Adsorbing material as well as preparation method and application thereof
A cost-effective adsorption material made from volcanic rock, sludge, fly ash, and steel slag addresses the inefficiencies of existing adsorbents by providing high adsorption capacity for phosphorus and fluorine in acidic waters, leveraging a simple preparation process and solid waste utilization.
Patent Information
- Application Number
- CN202411765603.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing adsorbents for phosphorus and fluorine removal, such as activated carbon, natural clay minerals, and mesoporous materials, are costly, inefficient, or have complex preparation procedures, making them unsuitable for large-scale industrial applications in addressing phosphogypsum-related water pollution.
An adsorption material composed of porous volcanic rock, dried sludge from a water supply plant, fly ash, and steel slag, combined with a binder and foaming agent, is prepared through a simple process involving ultrasonic treatment and calcination, resulting in a high specific surface area and porosity, enhancing adsorption capacity for phosphorus and fluorine.
The adsorption material effectively removes phosphorus and fluorine from acidic water bodies with a high adsorption capacity and stability, utilizing solid waste materials to reduce production costs and improve water quality.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to an adsorption material and a preparation method and application thereof. Background Art
[0002] Phosphogypsum is a typical industrial solid waste produced during the wet production of phosphoric acid. The storage of phosphogypsum not only occupies a large amount of land, but also contains high concentrations of soluble phosphates and impurities such as fluorine, posing a serious risk of pollution to the surrounding soil and water. Phosphogypsum leaching pollution has become one of the important factors for the excessive water quality of the Yangtze River. Among them, phosphorus is a key factor in causing eutrophication of water bodies. At a lower concentration, it can lead to eutrophication and algal bloom; the accumulation of fluorine in the soil will change the physical and chemical properties of the soil, affect the activity of soil microorganisms and soil fertility, and thus have an adverse effect on the growth of crops. At the same time, if high-fluoride groundwater is used as a source of drinking water, it will also cause harm to human health, such as causing fluorosis, fluorosis and other symptoms of fluoride poisoning. At this stage, the methods for removing phosphorus and fluorine mainly include chemical methods, biological methods and adsorption methods. The adsorption method has been widely studied and applied because it is simpler, more efficient, stable and environmentally friendly.
[0003] However, traditional adsorbents such as activated carbon are expensive and have limited adsorption capacity for phosphorus and fluorine, making them unsuitable for large-scale industrial applications; natural clay minerals and biomass materials are not efficient in adsorbing phosphorus and fluorine; and new adsorbents such as mesoporous materials have complex preparation procedures, high costs, and poor economic efficiency. Therefore, it is of great significance to develop a low-cost adsorbent material with strong adsorption capacity for phosphorus and fluorine. Summary of the invention
[0004] The main purpose of the present invention is to provide an adsorption material, which has low cost and strong adsorption capacity for phosphorus and / or fluorine.
[0005] The present invention also provides a method for preparing the adsorption material, which can prepare the above-mentioned adsorption material, and has simple process and low cost.
[0006] The present invention also provides a water purification method, which uses an adsorbent including the above-mentioned adsorption material to purify the water body, thereby improving the adsorption capacity of phosphorus and / or fluorine.
[0007] In a first aspect, the present invention provides an adsorbent material having a specific surface area of 300 to 600 m 2 / g; the porosity of the adsorption material is greater than 40%; the raw materials of the adsorption material include the following components in parts by mass: 18 to 35 parts of porous volcanic rock, 6 to 11 parts of dried sludge from a water supply plant, 3 to 7 parts of fly ash, 6 to 14 parts of steel slag, 10 to 20 parts of a binder, and 5 to 10 parts of a foaming agent.
[0008] The adsorption material as described above, wherein the pH value of the adsorption material is 8-11.
[0009] The adsorption material as described above, wherein the porosity of the porous volcanic rock is greater than 30%; the bulk density of the porous volcanic rock is less than 2g / cm 3 ; The average particle size of the porous volcanic rock is 0.5~3cm.
[0010] The adsorption material as described above, the moisture content of the dried sludge from the water supply plant is less than 20%; the mass content of organic matter in the dried sludge from the water supply plant is less than 20%; the average particle size of the dried sludge from the water supply plant is less than 200μm; the total mass content of iron salts and aluminum salts in the dried sludge from the water supply plant is greater than 15%; and / or the average particle size of the fly ash is less than 80μm; and / or the average particle size of the steel slag is less than 200μm; the total mass content of calcium oxide, magnesium oxide, manganese oxide, and iron and aluminum oxides in the steel slag is greater than 40%; and / or the binder includes silicate cement and / or sulphoaluminate cement, preferably sulphoaluminate cement; and / or the foaming agent includes at least one of calcium carbonate, magnesium carbonate, and calcium bicarbonate.
[0011] In a second aspect, the present invention provides a method for preparing the adsorbent material as described above, comprising the following steps:
[0012] 1) Mixing a mixed system including porous volcanic rock, dried sludge from a water supply plant, fly ash, and steel slag with an acidic solution to obtain a first system; subjecting the first system to ultrasonic treatment and then allowing it to stand to obtain a first mixture;
[0013] 2) washing, filtering and drying the first mixture to obtain a second mixture;
[0014] 3) Pressing and calcining the second system including the second mixture, the binder material and the foaming agent to obtain the adsorption material.
[0015] According to the preparation method described above, the pH value of the acidic solution is 3-5; and / or the volume ratio of the mixed system to the acidic solution is 1:(1.5-2); and / or the acidic solution includes dilute hydrochloric acid and / or dilute sulfuric acid; and / or the power of the ultrasonic treatment is 0.3-0.6 W / mL, and the operation is paused for 10-20 seconds every 50-80 seconds, and the total operation time is 300-500 seconds.
[0016] In the preparation method as described above, the water content of the second mixture is less than 20%; and / or the temperature of the calcination treatment is greater than 500° C. and the time is greater than 1 hour.
[0017] In a third aspect, the present invention provides a method for purifying a water body, comprising the following steps: purifying the water body with an adsorbent, wherein the adsorbent comprises the adsorbent material as described above or the adsorbent material obtained by the preparation method as described above.
[0018] In the water purification method as described above, the water contains phosphorus and / or fluorine.
[0019] In the water purification method as described above, the water body includes the water body formed after the phosphogypsum reservoir is flushed with rainwater.
[0020] The adsorption material provided by the present invention includes porous volcanic rock, dried sludge from water supply plants, fly ash, steel slag and other solid waste materials, which realizes the resource utilization of solid waste and greatly reduces the production cost. The specific surface area of the adsorption material is 300-600m 2 / g, the porosity is greater than 40%, and it still has a strong adsorption capacity for phosphorus and / or fluorine under strong acidic conditions. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In a first aspect, the present invention provides an adsorbent material having a specific surface area of 300 to 600 m 2 / g; the porosity of the adsorption material is greater than 40%; the raw materials of the adsorption material include the following components in parts by mass: 18 to 35 parts of porous volcanic rock, 6 to 11 parts of dried sludge from a water supply plant, 3 to 7 parts of fly ash, 6 to 14 parts of steel slag, 10 to 20 parts of a binder, and 5 to 10 parts of a foaming agent.
[0023] For example, the specific surface area of the adsorbent material may be 300 m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g or a range consisting of any two thereof. The porosity of the adsorbent material may be 42%, 45%, 47%, 50%, 60%, 70%, 80% or a range consisting of any two thereof. The number of portions of porous volcanic rock may be 18, 20, 25, 30, 35 or a range consisting of any two thereof. The number of portions of dried sludge from a water supply plant may be 6, 7, 8, 9, 10, 11 or a range consisting of any two thereof. The number of portions of fly ash may be 3, 4, 5, 6, 7 or a range consisting of any two thereof. The number of portions of steel slag may be 6, 7, 8, 9, 10, 11, 12, 13, 14 or a range consisting of any two thereof. The number of portions of cementitious material may be 10, 12, 15, 17, 20 or a range consisting of any two thereof. The number of portions of foaming agent may be 5, 6, 7, 8, 9, 10 or a range consisting of any two thereof.
[0024] It can be understood that the specific surface area is one of the important indicators for measuring the performance of adsorption materials. When the specific surface area is within the above range, the surface of the adsorption material can provide more adsorption sites, which can enhance the adsorption capacity of phosphorus and / or fluorine. The porosity within the above range means that there are more pore structures inside the adsorption material. These pores not only increase the specific surface area of the adsorption material, but also provide more channels and storage space for the adsorption process, which is conducive to the rapid diffusion and storage of phosphorus and / or fluorine.
[0025] The porous volcanic rock in the adsorption material serves as a carrier of the adsorption material, has a porous structure, a high specific surface area, and a high porosity. The porous volcanic rock can be a basaltic or rhyolitic volcanic rock. The dried sludge, fly ash, and steel slag of the water supply plant are used as adsorption materials and are evenly filled in the pores of the porous volcanic rock. They can adapt to the strong acidic characteristics of special water bodies and greatly enhance the adsorption capacity of the porous volcanic rock for phosphorus and / or fluorine. In the present invention, the dried sludge of the water supply plant is generally obtained by drying the water supply sludge. The water supply sludge can come from the water supply plant and can also be called dried water supply sludge. Fly ash generally comes from the residue of a thermal power plant or an industrial furnace. Steel slag generally comes from the smelting waste of a smelter, which is an alkaline fine-grained smelting slag after grinding and screening. The binder plays the role of bonding the components, so that the adsorption material has good mechanical strength and stability. The introduction of the foaming agent can form a porous structure in the adsorption material, so that the adsorption material has a suitable pore structure, which can improve the surface area and porosity of the adsorption material and enhance the adsorption capacity of phosphorus and / or fluorine.
[0026] The water permeability coefficient of the adsorption material provided by the present invention is greater than 1×10 -2cm / s, compressive strength greater than 3MPa, organic matter content less than 1%, organic matter can include sugars, proteins, lipids, cellulose, hemicellulose and lignin, microbial flora and its metabolites and other organic compounds. The maximum saturated adsorption capacity of the adsorbent material of the present invention for phosphorus is greater than 15mg / g, and the maximum saturated adsorption capacity for fluorine is greater than 10mg / g. The adsorbent material can simultaneously remove phosphorus and fluorine from polluted water, and the 24h removal rate is above 85%.
[0027] The adsorption material provided by the present invention includes porous volcanic rock, dried sludge from water supply plants, fly ash, steel slag and other solid waste materials, which realizes the resource utilization of solid waste and greatly reduces the production cost. The specific surface area of the adsorption material is 300-600m 2 / g, the porosity is greater than 40%, and it still has a strong adsorption capacity for phosphorus and / or fluorine under strong acidic conditions.
[0028] In some embodiments of the present invention, the pH value of the adsorbent material is 8-11, for example, it can be 8, 8.5, 9, 9.5, 10, 10.5, 11 or a range consisting of any two thereof.
[0029] The pH value of the adsorbent material in the present invention is within the above range, and can be applied to the adsorption of phosphorus and / or fluorine in water bodies with a pH value range of 3.0 to 11.0, especially the adsorption of phosphorus and / or fluorine in acidic water bodies. It can neutralize the hydrogen ions in the acidic solution with acid-base, which is beneficial to reduce the acidity of the acidic solution, change the solubility and existence form of the substance in the acidic solution, and thus help to improve the adsorption effect. In addition, the alkaline adsorbent material can also react chemically with specific substances in the acidic solution to form chemical bonds. This chemical adsorption is stronger than physical adsorption and can effectively remove phosphorus and / or fluorine in the solution.
[0030] In some embodiments of the present invention, the porosity of the porous volcanic rock is greater than 30%; the bulk density of the porous volcanic rock is less than 2g / cm 3 ; The average particle size of the porous volcanic rock is 0.5~3cm.
[0031] For example, the porosity of the porous volcanic rock may be 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, or any two thereof. The bulk density of the porous volcanic rock may be 1.9 g / cm 3 , 1.8g / cm 3 , 1.7g / cm 3 , 1.6g / cm 3 , 1.5g / cm 3 , 1g / cm 3 , 0.8g / cm3 , 0.5g / cm 3 The average particle size of the porous volcanic rock may be 0.5 cm, 1 cm, 1.5 cm, 2 cm, 2.5 cm, 3 cm, or a range consisting of any two thereof.
[0032] It can be understood that bulk density refers to the weight of an object per unit volume. The porous volcanic rock in the present invention is obtained after crushing and screening, and its porosity, bulk density and average particle size are within the above ranges, which can increase the specific surface area of the porous volcanic rock and improve its adsorption capacity, which is conducive to more adsorption materials filling the pores of the porous volcanic rock, and further improve the adsorption capacity of the adsorption material for phosphorus and / or fluorine.
[0033] In some embodiments of the present invention, the moisture content of the dried sludge from the water plant is less than 20%; the organic matter mass content of the dried sludge from the water plant is less than 20%; the average particle size of the dried sludge from the water plant is less than 200 μm; and the total mass content of iron salts and aluminum salts in the dried sludge from the water plant is greater than 15%.
[0034] In some embodiments, the average particle size of the fly ash is less than 80 μm.
[0035] In some embodiments, the average particle size of the steel slag is less than 200 μm; the total mass content of calcium oxide, magnesium oxide, manganese oxide, and iron and aluminum oxides in the steel slag is greater than 40%.
[0036] In some embodiments, the cementitious material comprises silicate cement and / or sulphoaluminate cement, preferably sulphoaluminate cement.
[0037] In some embodiments, the foaming agent includes at least one of calcium carbonate, magnesium carbonate, and calcium bicarbonate.
[0038] Exemplarily, the moisture content of the dried sludge of the water supply plant can be 1%, 5%, 10%, 15%, 17%, 19% or a range consisting of any two thereof. The mass content of organic matter in the dried sludge of the water supply plant can be 1%, 5%, 10%, 15%, 17%, 19% or a range consisting of any two thereof. The average particle size of the dried sludge of the water supply plant can be 50μm, 100μm, 150μm, 160μm, 180μm, 190μm or a range consisting of any two thereof. The total mass content of iron salts and aluminum salts in the dried sludge of the water supply plant can be 16%, 18%, 20%, 25%, 30%, 40%, 50%, 60% or a range consisting of any two thereof. The average particle size of fly ash can be 40μm, 50μm, 60μm, 70μm, 75μm, 79μm or a range consisting of any two thereof. The average particle size of the steel slag can be 50 μm, 100 μm, 150 μm, 160 μm, 180 μm, 190 μm or a range consisting of any two thereof. The total mass content of calcium oxide, magnesium oxide, and iron and aluminum oxides in the steel slag can be 41%, 45%, 50%, 60%, 70%, 80% or a range consisting of any two thereof.
[0039] The dried sludge of the water supply plant in the present invention needs to be ground before use so that its average particle size is less than 200 μm, so that more dried sludge can be adsorbed in the pore structure of porous volcanic rock, thereby improving the adsorption capacity of the adsorbent material for phosphorus and / or fluorine. The moisture content of the dried sludge of the water supply plant is within the above range, which can absorb more water, thereby improving the adsorption capacity of the adsorbent material for phosphorus and / or fluorine in water. The organic matter mass content of the dried sludge of the water supply plant is within the above range, which can avoid excessive organic matter from reacting with substances in the water, causing the adsorbent material to be corrupted, and reducing the structural stability and service life of the adsorbent material, wherein the organic matter can include sugars, proteins, lipids, cellulose, hemicellulose and lignin, microbial flora and its metabolites and other organic compounds. The total mass content of iron salts and aluminum salts in the dried sludge of the water supply plant is within the above range, which can be combined with phosphate and fluoride ions under acidic conditions to form precipitation, thereby enhancing the adsorption capacity of the adsorbent material for phosphorus and / or fluorine.
[0040] The average particle size of the fly ash in the present invention is less than 80 μm, so that more fly ash can be adsorbed in the pore structure of the porous volcanic rock, thereby improving the adsorption capacity of the adsorption material for phosphorus and / or fluorine.
[0041] The average particle size of the steel slag in the present invention is less than 200 μm, so that more steel slag can be adsorbed in the pore structure of the porous volcanic rock, thereby improving the adsorption capacity of the adsorbent material for phosphorus and / or fluorine. Calcium oxide, magnesium oxide, and manganese oxide in the steel slag are alkaline substances, which can adjust the pH value of the adsorbent material to make the pH value of the adsorbent material appropriate. The total mass content of iron and aluminum oxides in the steel slag is greater than 40%, which can combine with phosphate and fluoride ions under acidic conditions to form precipitation, thereby enhancing the adsorption capacity of the adsorbent material for phosphorus and / or fluorine.
[0042] In the present invention, the cementing material includes silicate cement and / or sulphoaluminate cement, preferably sulphoaluminate cement, which can further firmly combine the above materials to form a stable adsorption material. The foaming agent includes at least one of calcium carbonate, magnesium carbonate, and calcium bicarbonate, preferably calcium bicarbonate and calcium carbonate, with a particle size of 3-5 mm, which can further make the adsorption material have a better pore structure and a suitable specific surface area, thereby enhancing the adsorption capacity of the adsorption material for phosphorus and / or fluorine.
[0043] The present invention does not limit the test method of the average particle size of dried sludge, fly ash and steel slag of the water supply plant. For example, a laser particle size analyzer can be used for testing.
[0044] In a second aspect, the present invention provides a method for preparing the adsorbent material as described above, comprising the following steps:
[0045] 1) Mixing a mixed system including porous volcanic rock, dried sludge from a water supply plant, fly ash, and steel slag with an acidic solution to obtain a first system; subjecting the first system to ultrasonic treatment and then allowing it to stand to obtain a first mixture;
[0046] 2) washing, filtering and drying the first mixture to obtain a second mixture;
[0047] 3) Pressing and calcining the second system including the second mixture, the binder material and the foaming agent to obtain the adsorption material.
[0048] In step 1) of the present invention, a certain mass of porous volcanic rock, dried sludge from a water supply plant, fly ash, and steel slag can be mixed, placed in an acidic solution, and then left to stand for 0.5-2 hours after ultrasonic vibration treatment to obtain a first mixture. Ultrasonic vibration treatment can make the fine-grained dried sludge from a water supply plant, fly ash, and steel slag evenly distributed in the pore size of the volcanic rock, greatly enhancing the adsorption capacity of the adsorbent material for phosphorus and / or fluorine. Vibration in an acidic solution can dissolve the soluble substances on the surface of each material, further increase the specific surface area of the adsorbent material, and activate the adsorption activity of the adsorbent material.
[0049] In step 2), the first mixture obtained above is washed, filtered out and dried to remove impurities and moisture in each material, so as to obtain a relatively pure second mixture.
[0050] In step 3), the second mixture, the binder material and the foaming agent obtained above are fully mixed to form a second system, and the second system is placed in a mold for compression molding and then calcined at high temperature to obtain an adsorbent material. High-temperature calcination can remove organic components in the adsorbent material, increase porosity, and modify the adsorbent material to further enhance its adsorption activity.
[0051] The preparation method of the adsorption material provided by the present invention has simple process and low cost. The prepared adsorption material has a stable structure and strong resistance to pH interference. It is suitable for water bodies downstream of strongly acidic, high-phosphorus and high-fluorine phosphogypsum reservoirs. The effect of removing phosphorus and / or fluorine is stable and the saturated adsorption capacity is large.
[0052] In some embodiments of the present invention, the pH value of the acidic solution is 3-5.
[0053] In some embodiments, the volume ratio of the mixed system to the acidic solution is 1:(1.5-2).
[0054] In some embodiments, the acidic solution includes dilute hydrochloric acid and / or dilute sulfuric acid.
[0055] In some embodiments, the power of the ultrasonic treatment is 0.3-0.6 W / mL, and the operation is performed for 50-80 seconds with a pause of 10-20 seconds, and the total operation time is 300-500 seconds.
[0056] Exemplarily, the pH value of the acidic solution can be 3, 3.2, 3.5, 3.7, 4, 4.2, 4.5, 4.7, 5 or any two of them. The volume ratio of the mixed system to the acidic solution can be 1: 1.5, 1: 1.6, 1: 1.7, 1: 1.8, 1: 1.9, 1: 2 or any two of them. The power of the ultrasonic treatment can be 0.3W / mL, 0.35W / mL, 0.4W / mL, 0.45W / mL, 0.5W / mL, 0.55W / mL, 0.6W / mL or any two of them. The running time can be 50s, 60s, 65s, 70s, 80s or any two of them. The pause time can be 10s, 13s, 15s, 18s, 20s or any two of them. The total running time may be 300s, 320s, 350s, 370s, 400s, 420s, 450s, 470s, 500s, or a range consisting of any two of them.
[0057] The pH value of the acidic solution in the present invention is 3-5, and the acidic solution can be dilute hydrochloric acid and / or dilute sulfuric acid, and the volume ratio of the mixed system to the acidic solution is 1:(1.5-2), which can further dissolve the soluble substances on the surface of each material, increase the specific surface area of the adsorption material, and activate the adsorption activity of the adsorption material.
[0058] The conditions of the ultrasonic treatment in the present invention are within the above range, which can further make the fine-grained dried sludge, fly ash and steel slag of the water supply plant evenly distributed in the pore size of the volcanic rock, enhance the adsorption capacity of the adsorbent material for phosphorus and / or fluorine; and improve the dissolution effect of the acidic solution on the soluble substances on the surface of the material.
[0059] In some embodiments of the present invention, the water content of the second mixture is less than 20%.
[0060] In some embodiments, the calcination treatment is performed at a temperature greater than 500° C. and for a time greater than 1 h.
[0061] For example, the moisture content of the second mixture may be 1%, 5%, 10%, 15%, 17%, 19%, or any two thereof. The temperature of the calcination treatment may be 510° C., 550° C., 600° C., 700° C., 800° C., 900° C., 1000° C., or any two thereof. The time of the calcination treatment may be 1.5 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, or any two thereof.
[0062] The moisture content of the second mixture in the present invention is within the above range, which is conducive to the subsequent pressing and calcination after mixing with the binder and the foaming agent, so that the moisture content of the final adsorption material is lower and more water can be absorbed, thereby improving the adsorption capacity of the adsorption material for phosphorus and / or fluorine in water.
[0063] The temperature and time of the calcination treatment in the present invention are within the above ranges, which can fully remove the organic components in the adsorption material, increase the porosity, and modify the adsorption material to further enhance its adsorption activity.
[0064] In a third aspect, the present invention provides a method for purifying a water body, comprising the following steps: purifying the water body with an adsorbent, wherein the adsorbent comprises the adsorbent material as described above, or the adsorbent material obtained by the preparation method as described above.
[0065] Specifically, the adsorbent material can be placed in the water to be purified or crushed and placed in the ecological wetland as filler. When the adsorbent material is used as a purification material for the water to be purified, it is used by evenly laying it on the bottom of the water, in the water or on the slope, and the usage amount is 0.5-10g / L. When the adsorbent material is used as a wetland filler, it needs to be crushed into two parts: coarse-grained filler (particle size 3~6cm, median particle size greater than 4cm) and fine-grained filler (particle size 0.1~3cm, median particle size less than 1cm). The coarse-grained filler is placed at the bottom with a laying thickness of 30~50cm, and the fine-grained filler is placed at the top with a laying thickness of 30~50cm. Water penetrates from the fine-grained filler to the coarse-grained filler, which can enhance the adsorption effect.
[0066] The water purification method provided by the present invention adopts an adsorbent to purify the water, and the adsorbent includes the above-mentioned adsorption material. Therefore, the water purification method can improve the adsorption capacity of phosphorus and / or fluorine.
[0067] In some embodiments of the present invention, the water body contains phosphorus and / or fluorine, and the adsorption material can have a strong adsorption capacity for the phosphorus and / or fluorine in the water body.
[0068] In some embodiments of the present invention, the water body includes the water body formed after flushing the phosphogypsum reservoir with rainwater.
[0069] The water body of the present invention includes the water body formed after the phosphogypsum reservoir is flushed with rainwater, that is, the water body is strongly acidic and contains a large amount of phosphorus and / or fluorine. The water body is purified by using the above-mentioned adsorption material, which can have a strong absorption capacity for phosphorus and / or fluorine in the water body.
[0070] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0071] Example 1
[0072] The preparation method of the adsorbent material of this embodiment comprises the following steps:
[0073] 1) Take 30 parts by mass of porous volcanic rock, 10 parts by mass of dried sludge from a water supply plant, 5 parts by mass of fly ash, and 12 parts by mass of steel slag, mix them to obtain a mixed system, and place the mixed system in a dilute hydrochloric acid solution (pH value is 4) to mix to obtain a first system, wherein the volume ratio of the mixed system to the dilute hydrochloric acid solution is 1:2. The first system is treated with ultrasonic vibration and then allowed to stand for 1 hour to obtain a first mixture. The power of the ultrasonic treatment is 0.5 W / mL, and it is paused for 10 seconds every 60 seconds of operation, and the total operation time is 420 seconds. The porous volcanic rock is rhyolitic volcanic rock, and the porosity of the porous volcanic rock is 42.7%, and the bulk density is 1.12 g / cm 3, with an average particle size of 2.3cm; the dried sludge is obtained after drying the water supply sludge. The water supply sludge comes from the water supply plant. The moisture content of the dried sludge is 15.8%, the average particle size is 163μm, the mass content of organic matter is 11.5%, and the total mass content of iron and aluminum salts in the dried sludge of the water supply plant is 23.7%; the fly ash comes from the thermal power plant, and the average particle size of the fly ash is 37μm; the steel slag comes from the smelting waste of the smelter. After grinding and screening, the average particle size of the steel slag is 112μm, and the total mass content of calcium oxide, magnesium oxide, manganese oxide, and iron and aluminum oxides in the steel slag is 56.7%.
[0074] 2) The first mixture was washed with water, filtered out and dried to obtain a second mixture, wherein the moisture content of the second mixture was 18.5%. The second mixture was fully mixed with 15 parts by mass of the binder material sulphoaluminate cement and 7 parts by mass of the foaming agent calcium bicarbonate, placed in a mold for pressing and then calcined at 800°C for 2 hours to obtain an adsorbent material with a specific surface area of 541m 2 / g, porosity is 61.8% and pH value is 10.78.
[0075] The method for water purification of this embodiment comprises the following steps:
[0076] The adsorption material is evenly laid on the bottom of the water to be purified. The water to be purified contains phosphorus and fluorine, including the water formed after the phosphogypsum reservoir is flushed with rainwater. The phosphorus and fluorine contents are 76.73 mg / L and 15.87 mg / L, respectively, and the pH value is 4.9. The adsorption experiment of the adsorption material is divided into two groups. The usage of the first group is 0.5 g / L, and the saturated adsorption capacity of the adsorption material for phosphorus and fluorine is tested; the usage of the second group is 2 g / L, and the 24h removal rate of phosphorus and fluorine by the adsorption material is tested. The results are shown in Table 3.
[0077] Embodiment 2-9
[0078] The preparation method of the adsorbent material and the water purification method of Examples 2-9 are basically the same as those of Example 1, except that one or more of the items are changed. The results are shown in Tables 1-3.
[0079] Example 10
[0080] The preparation method and water purification method of the adsorbent material of Example 10 are basically the same as those of Example 1, except that in step 3), the adsorbent material is crushed into coarse particles (particle size 4-6 cm, median particle size 5.12 cm) and fine particles (particle size 0.2-1.5 cm, median particle size 0.71 cm), the coarse-grained filler is laid on the lower part of the wetland to be purified, with a laying thickness of 40 cm, and the fine-grained filler is laid on the upper part of the coarse-grained filler, with a laying thickness of 30 cm. The water body at the inlet of the wetland to be purified is the water body formed after the phosphogypsum reservoir is flushed with rainwater, with a pH value of 3.8, wherein the contents of phosphorus and fluorine are 27.46 mg / L and 3.62 mg / L, respectively. After adsorption by the adsorbent material, the contents of phosphorus and fluorine in the water body at the outlet are 0.85 mg / L and 0.13 mg / L, respectively.
[0081] Comparative Example 1
[0082] The preparation method of the adsorbent material and the water purification method of Comparative Example 1 are basically the same as those of Example 1, except that no foaming agent is added. The results are shown in Tables 1-3.
[0083] Comparative Example 2
[0084] The preparation method of the adsorption material and the water purification method of Comparative Example 2 are basically the same as those of Example 1, except that no dried sludge from a water supply plant is added. The results are shown in Tables 1-3.
[0085] Comparative Example 3
[0086] The preparation method of the adsorption material and the water purification method of Comparative Example 3 are basically the same as those of Example 1, except that no steel slag is added. The results are shown in Tables 1-3.
[0087] Test example
[0088] 1. Saturated adsorption capacity: refers to the maximum mass of pollutants that can be adsorbed by a unit mass of adsorption material. The test method is the static adsorption method. A small amount of adsorption material (mass is M) is placed in a solution rich in pollutants (volume is V) for a long enough time until the concentration of pollutants in the solution no longer changes. The concentrations of pollutants in the solution before and after adsorption are measured as C0 and C1 respectively. The saturated adsorption capacity is (C0-C1)×V / M, and the unit is mg / g.
[0089] 2. 24h removal rate: refers to the removal rate of pollutants in the solution 24 hours after adding sufficient adsorption material. The calculation method is to measure the concentration of pollutants in the solution before adsorption (C0), and the concentration after 24 hours is C1. The removal rate (%) is (C0-C1) / C0×100%.
[0090] 3. Specific surface area: refers to the total area per unit mass of material, measured by gas adsorption BET method. The test steps refer to standard GB / T 19587 "Determination of specific surface area of solid substances by gas adsorption BET method".
[0091] 4. Porosity: refers to the ratio of the sum of the pore space volumes in the sample to the volume of the sample. It is measured by volume measurement. Take a container of known volume (V), fill it with the sample to be tested and weigh it (M1), then continue to add water (density is ρ, which can be 1g / cm 3 ), until the liquid level reaches the top of the container and stops falling, then weigh (M2). If the sample is light, wrap the top of the container with a piece of gauze and remove the gauze when weighing. Porosity (%) = (M2-M1) / (ρ×V)×100%.
[0092] Table 1
[0093]
[0094] Table 2
[0095]
[0096] Table 3
[0097]
[0098] As can be seen from Tables 1-3, compared with the comparative example, the adsorption material provided by the present invention includes solid waste materials such as porous volcanic rock, dried sludge from a water supply plant, fly ash, and steel slag, which realizes the resource utilization of solid waste and greatly reduces the production cost. The specific surface area of the adsorption material is 300-600m 2 / g, the porosity is greater than 40%, and it has a strong adsorption capacity for phosphorus and / or fluorine under strong acidic conditions.
[0099] From the comparison between Example 1 and Comparative Examples 1-3, it can be seen that the adsorption material provided by the present invention has a large saturated adsorption capacity for phosphorus and fluorine.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An adsorption material, characterized in that: The specific surface area of the adsorption material is 300-600m 2 / g; the porosity of the adsorption material is greater than 40%; The raw materials of the adsorption material include the following components in parts by mass: 18 to 35 parts of porous volcanic rock, 6 to 11 parts of dried sludge from a water supply plant, 3 to 7 parts of fly ash, 6 to 14 parts of steel slag, 10 to 20 parts of a cementitious material, and 5 to 10 parts of a foaming agent.
2. The adsorption material according to claim 1, characterized in that The pH value of the adsorption material is 8-11.
3. The adsorption material according to claim 1 or 2, characterized in that: The porosity of the porous volcanic rock is greater than 30%; the bulk density of the porous volcanic rock is less than 2g / cm 3 ; The average particle size of the porous volcanic rock is 0.5~3cm.
4. The adsorption material according to claim 3, characterized in that The moisture content of the dried sludge from the water supply plant is less than 20%; the organic matter mass content of the dried sludge from the water supply plant is less than 20%; the average particle size of the dried sludge from the water supply plant is less than 200 μm; the total mass content of iron salts and aluminum salts in the dried sludge from the water supply plant is greater than 15%; and / or, the average particle size of the fly ash is less than 80 μm; and / or, the average particle size of the steel slag is less than 200 μm; the total mass content of calcium oxide, magnesium oxide, manganese oxide, and iron and aluminum oxides in the steel slag is greater than 40%; and / or, the cementitious material comprises silicate cement and / or sulphoaluminate cement; And / or, the foaming agent includes at least one of calcium carbonate, magnesium carbonate and calcium bicarbonate.
5. A method for preparing the adsorption material according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Mixing a mixed system including porous volcanic rock, dried sludge from a water supply plant, fly ash, and steel slag with an acidic solution to obtain a first system; subjecting the first system to ultrasonic treatment and then allowing it to stand to obtain a first mixture; 2) washing, filtering and drying the first mixture to obtain a second mixture; 3) Pressing and calcining the second system including the second mixture, the binder material and the foaming agent to obtain the adsorption material.
6. The method for preparing an adsorbent material according to claim 5, characterized in that: The pH value of the acidic solution is 3-5; And / or, the volume ratio of the mixed system to the acidic solution is 1:(1.5-2); And / or, the acidic solution includes dilute hydrochloric acid and / or dilute sulfuric acid; And / or, the power of the ultrasonic treatment is 0.3-0.6 W / mL, and the operation is performed for 50-80 seconds with a pause of 10-20 seconds, and the total operation time is 300-500 seconds.
7. The method for preparing an adsorbent material according to claim 5, characterized in that: The moisture content of the second mixture is less than 20%; And / or, the calcination treatment temperature is greater than 500° C. and the time is greater than 1 hour.
8. A water purification method, characterized in that: The method comprises the following steps: purifying the water body by using an adsorbent, wherein the adsorbent comprises the adsorbent material according to any one of claims 1 to 5 or the adsorbent material prepared by the preparation method according to claim 6 or 7.
9. The water purification method according to claim 8, characterized in that: The water body contains phosphorus and / or fluorine.
10. The water purification method according to claim 8, characterized in that: The water body includes the water body formed after the phosphogypsum reservoir is flushed with rainwater.
Citation Information
Patent Citations
Phosphorus adsorbent prepared from sludge from water supply plants and application of phosphorus adsorbent
CN109908860A
Constructed wetland nitrogen and phosphorus removal filler and preparation method thereof
CN117185489A
Nitrogen and phosphorus adsorbent for biogas slurry as well as preparation method and application of nitrogen and phosphorus adsorbent
CN118204054A